2012
DOI: 10.1080/01140671.2011.604091
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2,4-DP (2,4-dichlorophenoxypropionic acid) plant growth regulator on fruit size and yield of Valencia oranges (Citrus sinensisOsb.)

Abstract: The Valencia orange is a high-quality fruit grown in Turkey; however, small fruit sizes and high fruit discard percentages are common in Valencia oranges. Small fruit size is the main factor limiting the marketing of Valencia oranges; thus, synthetic auxins are commonly used to enhance the size of citrus fruit. The objective of the present study was to observe the effects of 2,4-dichlorophenoxypropionic acid (2,4-DP) on the fruit size, yield and quality of Valencia oranges from 29-year-old trees budded on sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
(23 reference statements)
1
3
0
1
Order By: Relevance
“…Comparing the unpruned control group, which had the lowest juice volume, the fruit from trees pruned at 75 percent pruning level had the highest juice volume. These findings support the previous research by Yildirim et al [41] who found that pruning had a significant positive impact on the juice content of Star Ruby grapefruit. Pruning the 'Fermont' and 'Murcott' mandarin cultivars also significantly increased the fruit juice content, as stated by Hamdy [39].…”
Section: Juice Content Of Fruitsupporting
confidence: 92%
“…Comparing the unpruned control group, which had the lowest juice volume, the fruit from trees pruned at 75 percent pruning level had the highest juice volume. These findings support the previous research by Yildirim et al [41] who found that pruning had a significant positive impact on the juice content of Star Ruby grapefruit. Pruning the 'Fermont' and 'Murcott' mandarin cultivars also significantly increased the fruit juice content, as stated by Hamdy [39].…”
Section: Juice Content Of Fruitsupporting
confidence: 92%
“…1, the Cd(II) atom is coordinated to two oxygen atoms from two 2,4-D ligands and two nitrogen atoms of two imidazole molecules in the equatorial position, and two oxygen atoms of water molecules in the axial position, forming a CdO 4 N 2 octahedral geometry. The distance of Cd-N is 2.238(2) Å, which is shorter than the corresponding values in [Cd 2 (2,4-D) 4 (phen) 2 ] (phen = 1,10-phenanthroline), [7] [Cd(2,4-D) 2 (bib)] n (bib=1,4-bis(imidazol-1-yl)-butane) [24] and [Cd(2,4-D) 2 (4,4-bipy)] n (4,4'-Bipy = 4,4'-bipyridine). [25] The bond lengths of Cd(1)-O(1), Cd(1)-O(4) are 2.370(2), 2.394(2) Å, respectively, which are comparable with those of other Cd(II) complexes.…”
Section: Crystal Structural Descriptionmentioning
confidence: 59%
“…2,4-Dichlorophenoxyacetic acid (2,4-DH) is a member of arylcarboxylic acids family, and compounds belonging to it are commonly used as conventional fungicides, plant growth regulators and agricultural hebicides. 4 In recent years, an increasing interest can be observed on 2,4-DH coordination compounds, including complexes of transition metals such as Zn(II) 5 , Cd(II), [6][7] Cu(II), 8 Mn(II), 9 Co(II) 10 and Ni(II), 11 alkaline metals such as Ca(II), 12 and lanthanides like Gd 13 and Eu. 14 Several mixed-ligand coordination compounds with 2,4-DH and N-donor ligands, such as phenanthroline, 15 pyrazole, 16 pyridine, 17 pyrazine, 18 imidazole 19 and bipyridine, 20 are also known, and the results reveal that 2,4-D exhibits versatile binding and coordination modes.…”
Section: Introductionmentioning
confidence: 99%
“…Аналогічний ефект спостерігали за дії 2,4-дихлорфеноксіоцтової кислоти, застосованої на рослинах манго (Ahmed et al, 2012). 2,4-дихлорфеноксипропіонова кислота підвищувала урожайність апельсинів за рахунок зменшення опадання недозрілих плодів та збільшення їх розмірів і маси (Yіldіrım et al, 2012). Представник цієї ж групи ауксинівфенілоцтова кислота збільшувала концентрацію фотосинтетичних пігментів у зеленої мікроводорості Chlorella vulgaris (Piotrowska-Niczyporuk et al, 2014).…”
Section: вступunclassified